The Performance of Spot Photoscreener in 6 to 10 Weeks Infants in China: A Cross-Sectional Study - Yaoling Li; Jing Li; Huiyu Wang; Mingyang Du; Lirong Wei; Teng Su; Gang Ding; Xuehan Qian; Ning Hua (Journal of Ophthalmology)
Purpose. To compare the refractive errors measured by the Spot photoscreener (with or without cycloplegia) to cycloplegic retinoscopy in 6- to 10-week-old infants. Materials and Methods. 101 right eyes from 101 healthy infants aged 6 to 10 weeks were recruited for this cross-sectional observational study. Refractive errors were measured using Spot photoscreener before and after cycloplegia, as well as cycloplegic retinoscopy. Comparisons between the refractive measurements were performed using one-way ANOVA with the post hoc Tukey HSD test or Kruskal–Wallis test with the Steel–Dwass test according to the data normality. Pearson’s correlation test and 95% confidence intervals were calculated. The agreement was evaluated using a Bland–Altman plot with 95% limits of agreement of the differences. Results. Spot photoscreener was found to underestimate the spherical equivalent by 2.33 Diopters (D) in these infants. Following the induction of cycloplegia, the spherical equivalent measured by Spot photoscreener was in excellent agreement with cycloplegic retinoscopy with the mean difference of 0.01 D. Spot photoscreener overestimated cylindrical parameter by 0.2 D with poor agreement with cycloplegic retinoscopy no matter whether cycloplegia was induced. It had good agreement with cycloplegic retinoscopy in the J0 vector than the J45 vector measurement. Conclusions. With the induction of cycloplegia, Spot photoscreener can accurately evaluate spherical equivalent in hyperopic infants with mild-to-moderate astigmatism. While it may provide valuable measurements of astigmatism, discrepancies in cylinder and axis should be taken into account.